Strategic Assessment of the Ethiopian Mineral Sector : Final Report - World Bank Group (Washington, DC, 2014)
This report was commissioned with the aim to assist the Government of Ethiopia (GoE) in its efforts to develop the mining sector. Thus, the report has been produced in close cooperation with staff at the Ethiopian Ministry of Mines (MoM). Its findings are mostly based on desk top reviews of existing documents, on a large number of meetings, and interviews with affected and interested stakeholders, and also on some field work performed in the southern and western parts of the country. This report provides a review of the Ethiopian mining sector, and assesses its potential to contribute to sustainable economic growth and development. It further provides recommendations for the initiatives and actions that will be required for such development to take place, and it identifies the risk and opportunities that this entails. The need for this type of strategic analysis follows from the GoE ambition to, as part of the growth and transformation plan (GTP), and develop the mining sector to be a main pillar of the economy. The report is organized as follows: chapter one provides an introduction to the Ethiopian economy and the current contribution from mining, and describes general aspects of mineral sector development and how it may contribute to economic development. Chapter two presents the geological potential of the country, mineral occurrences, and mining and exploration projects. Chapter three presents possible scenarios for future mineral sector growth with economic implications, and further discusses industry linkages. Chapter's four to eleven include assessments of different mineral sector framework areas, and recommendations are provided in the end of each chapter. Chapter twelve presents' current infrastructure and development plans and finally, chapter thirteen presents a summary and prioritization of recommendations.